A Backstepping Sliding Mode Control of DC-DC Buck Converter - Boussadia, Ibtissem; Saoudi, Kamel; Bouchama, Ziyad; Aliskan, Ibrahim; Griche, Issam; Ayad, Mouloud (WYDAWNICTWO SIGMA-NOT SP ZOO, 2024)
In this paper, a Backstepping Sliding Mode controller is designed for the DC -DC buck converter under inherent nonlinearity and time variation. The proposed controller design is based on the integration both the merits of Backstepping control method and sliding mode control method (SMC). Based on Lyapunov synthesis approach, the derived controller can closely track change in reference output voltage and guarantees stability converge. Simulation results demonstrate the effectiveness and robustness of the proposed combination approach.
Keywords: Backstepping control; sliding mode control; buck converter; Engineering